السياسة الخارجية الجزائرية تجاه القضية الليبية 2011-2017 - هزيل, عبد الرحمان (جامعة الوادي University of Eloued, 2017)
ان اهم مافي السياسة الخارجية الجزائرية هي تمكسها بمحاولة المحافظة على الامن القومي المرتبط بمفهوم الامن الاقليمي وهدا مايعكس التوجه الدفاعي في السياسة الخارجية والتي برزت بشكل واضح في تعاملها مع القضايا الاقليمية وعليه فالجزائر ليست في معزل عن التطورات الاقليمية لدلك يجب تكييف السياسة الخارجية مع الضرورة لعب دور الفاعل الرئيسي في مختلف القضايا كون ان هده السياسة الدفاعية التي تنتهجها الجزائر تخدم مصلحة النظام السياسي انطلاقا من ابعاد كل مايهدد النخبة الحاكمة في الجزائر فمصلحة البقاء هي الكفيلة وحدها لفهم وتفسير سلوك الجزائر ازاء مختلف القضايا وهدا مايعكس النظرة الضيقة لصناع القرار في الاداء الخارجي للدولة الجزائرية تحت دريعة الحفاظ على الامن القومي الجزائري وتحقيق المصلحة الوطنية وهدا ماحاولنا مقاربته في موضوعنا هدا من خلال تتبع السياسة الخارجية الجزائرية تجاه القضية اللبيبة The most important objectives of the Algerian foreign policy are the attempts to preserve the national security associated with the concept of regional security. This is what reflects the defensive approach in foreign policy which has emerged clearly in its dealings with the regional issues. Therefore, Algeria is not isolated from regional developments. The main actor in the various issues is the fact that this defensive policy pursued by Algeria serves the interests of the political system from the exclusion of all the majors of the ruling elite in Algeria. The interest of survival is the only one capable of understanding and explaining Algeria's behavior towards the different Issues and Hedda Maaeks narrow view of the decision-makers in the external performance of the Algerian state under the Draah maintain the Algerian national security and national interest and Hedda Maholna in his approach to our subject Hedda through the Algerian foreign policy to follow the case Cores
نظم سياسية مقارنة والحكم الراشد
Keywords: السياسة الخارجية الجزائرية- القضية الليبية- العقيدة الامنية; Algerian foreign policy - the Libyan issue - the security doctrine